Nghiên cứu chế tạo vật liệu có độ bền nhiệt, bền cơ lý cao và hàm tro thấp từ cao su nitril - Hữu, Chu Chiến (Vietnam Journal of Chemistry, 2017)
In this paper, we present some research results on material  compositions based on nitril rubber in the aviation application. The material based on butadiene acrylonitril rubber containing 40 % acrylonitril and reinforced with phenol formaldehyde resin modified by fatty acid of nut shell oil which has gained good properties as tensile strength of 134 kG/cm2, elongation at break 35 %, the remaining elongation about 2 %, ash content 3.7 %. This composition can withstand  the temperature 3500 oC at presure 43.27 atm for 11.54s. The results show our material has satisfied the high technical requirement for this kind of materials. Keywords. Nitrile rubber, retardant rubber materials.